Հողամշակ ֆրեզի դանակների կողմից փխրեցված հողազանգվածի շպրտման ինտենսիվության նվազեցման տեխնիկատեխնոլոգիական միջոցառումների մշակում - Գրիգորյան, Ալբերտ; Թարվերդյան, Արշալույս; Ալթունյան, Արթուր (ՀԱԱՀ հիմնադրամ)
На интенсивность отбрасывания ножом почвенной массы при ротационной обработке почвы влияют конструктивнотехнологические параметры машины и физикомеханические свойства грунта. Исследованиями обосновано, что снизить интенсивность отбрасывания почвы возможно посредством выбора оптимальных параметров технологических процессов и усовершенствования конструкции ротационных ножей. В основу теоретического решения предложенной задачи взаимодействия ножа почвообрабатывающей фрезы с почвой легла модель косого удара двух тел в условиях вязкого трения. Rotary tillage often leads to the undesirable phenomenon of soil being thrown back by the rotary blade, which diminishes the technological quality of soil preparation. This is evidenced by the exposure of certain areas and the formation of grooves behind the working element in the already cultivated soil strip. The soil throwing intensity is influenced by the technological and structural parameters of the machine blades, as well as the physical and mechanical properties of the soil. However, it is evident that soil throwing intensity can be reduced by either optimally selecting the kinematic parameters of the tillage process or by structural improvement of rotary blades. The article explores the kinematics of soil throwing process, considering the impact interaction of the rotary working element with the soil based on the hypothesis of viscous friction under oblique impact. It has been also established that the most effective characteristics for reducing environmental resistance and soil thrust are endowed by the blades with a streamlined crosssectional profile.
Keywords: Ագրարային ճարտարագիտություն